IMPROVING TBO OF FREIGHT CAR BOGIES. GEOMETRY MODEL OF CENTER PAD WEAR - Muradian, L. A.; Podosonov, D. O. (Science and Transport Progress, 2017)
Purpose. The scientific work is aimed to: 1) analyze the technical condition of freight cars and technological methods used in the repair; 2) identify possible ways to improve resource of freight car bogies; 3) develop a mathematical model to describe the wear geometry of the original surface of bogie center pad at the corresponding life cycle of a freight car. Methodology. In order to solve the problem complex of increasing TBO of freight car bogies the methods for the synthesis, analysis and systematic approach were used. In addition, the use of mathematical modeling unit, solid state physics, the theory of friction and wear of solids. Findings. The analysis of the technical condition of freight cars has shown that up to 15% of the faults falls on the bogies. A separate element of the repaired bogie is a bolster. At this the center pad is recovered most often. The center pad wear is uneven and the technological methods used for the repair, do not allow providing uniform wear due to which there is a need in premature repairs. One of the ways to improve the center pad resource during repair is the application of welding or sputtering deposition, but with providing discrete strength and durability in the longitudinal and transverse directions of the car axis, respectively. In order to establish the boundaries of the distribution of renewable material along the center pad diameter it was considered the fatigue wear process in cooperation with center plate and described the geometry of the surface of the center pad wear. Originality. Technical condition of freight car bogies according to wear criterion was analyzed in the paper. It is shown that the dynamics of bogie faults has a positive character. In addition, a significant place among the repaired parts takes the bolster, and a special loaded place is the center pad. To describe the geometry of wear for the first time a mathematical model for determining the initial surface of the center pad in the relevant life cycle of freight car bogie was proposed. Practical value. The results allow us to establish the geometry of the wear surface bolster center pad when interacting with center plate of freight car from a position of occurrence of fatigue wear, that is, on the strength criterion.